2016
DOI: 10.18632/oncotarget.6893
|View full text |Cite
|
Sign up to set email alerts
|

Increased hepatic receptor interacting protein kinase 3 expression due to impaired proteasomal functions contributes to alcohol-induced steatosis and liver injury

Abstract: Chronic alcohol exposure increased hepatic receptor-interacting protein kinase (RIP) 3 expression and necroptosis in the liver but its mechanisms are unclear. In the present study, we demonstrated that chronic alcohol feeding plus binge (Gao-binge) increased RIP3 but not RIP1 protein levels in mouse livers. RIP3 knockout mice had decreased serum alanine amino transferase activity and hepatic steatosis but had no effect on hepatic neutrophil infiltration compared with wild type mice after Gao-binge alcohol trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
97
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(102 citation statements)
references
References 51 publications
5
97
0
Order By: Relevance
“…Necroptosis, a caspase-independent form of programmed cell death, also contributes to ethanol-induced liver injury [22, 33]. Because TNFα is an important activator of the necroptotic pathway [22,33], we also expected for necroptosis to be reduced in C5aR−/− mice compared to WT, since they expressed less TNFα in liver after chronic ethanol exposure.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Necroptosis, a caspase-independent form of programmed cell death, also contributes to ethanol-induced liver injury [22, 33]. Because TNFα is an important activator of the necroptotic pathway [22,33], we also expected for necroptosis to be reduced in C5aR−/− mice compared to WT, since they expressed less TNFα in liver after chronic ethanol exposure.…”
Section: Resultsmentioning
confidence: 99%
“…Because TNFα is an important activator of the necroptotic pathway [22,33], we also expected for necroptosis to be reduced in C5aR−/− mice compared to WT, since they expressed less TNFα in liver after chronic ethanol exposure. Ethanol feeding increased the expression of receptor interacting protein kinase 3 (RIP3), an important effector protein in necroptosis, in the centralobular zone in WT mice; this induction was similar in C5aR−/− mice (Figure 3B/D).…”
Section: Resultsmentioning
confidence: 99%
“…43 It should be noted that we and others recently demonstrated that the expression levels of RIP1 and RIP3 are remarkably higher in immune cells than in hepatocytes. 39,44 Therefore, it is highly likely that the functions of RIP1 and RIP3 in nonparenchymal cells may play important roles in LPS/GalN/ZVD-induced liver injury, which could be different from their direct role in cultured hepatocytes. Indeed, we found the mRNA levels of TNF-a and IL-1b were significantly higher in the livers of mice treated with RIP1 inhibitor and in RIP3 KO mouse livers after LPS/ GalN/ZVD administration.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the Ripk3 −/− genotype, the intraperitoneal delivery of Ripk3 -targeting antisense oligonucleotides, or the administration of dabrafenib (an FDA-approved inhibitor of oncogenic BRAF that also suppresses RIPK3 kinase activity) provides considerable hepatoprotection in mouse models of acetaminophen toxicity (134, 170, 171), concanavalin A–driven hepatitis (134), ethanol and dietary intoxication (172, 173), and nonalcoholic steatohepatitis (NASH) (174, 175). Along similar lines, mice treated with Nec-1 exhibit an increased resistance to the hepatotoxic effects of acetaminophen as compared with control animals (134).…”
Section: Pathophysiological Relevance Of Necroptosismentioning
confidence: 99%